Morfologia comparada da cabeça de Pentatomidae (Hemiptera: Heteroptera) - Barreiro, Maira dos Santos [UNIFESP] (2015)
The heteropteran head presents a high specialization level, making this group known for having, among other features, their piercing and sucking mouthparts in the anterior part of the head. Pentatomidae is the forth most diversified stink bug family. Its head is similar to those of all heteropterous, with variation on the size and shape of its structures, as the mandibular plates, clipeous, bucula and labium, with are very important to differentiate the Pentatomidae subfamilies and tribes. These variations gives this group numerous specializations and the head presents evidences of the evolutionary success of these organisms. The understanding of the head morphology and associated structures is extremely important to amplify the knowledge of this group, assists the taxonomy and provide essential information to investigate the phylogenetic relationships and the diversity of feeding habitats of Pentatomidae. This work aims to understand how the morphololgical variation ocurr in this tagma and to check if it is possible to recognize lineages through the head morphology and understand how the morphological variation is present in this tagma. To achieve this, the head morphology was compared among the Pentatomidae genus and was described for the recognized groups. Forty one important characters were raised and it was possible to elucidate some question about the head delimitation, the development of the structures and witch character describe them better. Based on the detailed characterization of the structures of the head it was possible to highlight the morphological variations of the head and understand which features are important in order to define and differentiate the Pentatomidae groups. Twenty-two lineages recognized by the head morphology are congruent with the subfamilies and tribes of the current Pentatomidae classification. Four more groups were recognized through groupping of genus that share the morphology of the head. Characteristics that define the groups were determined and all head structures were important for the group?s differentiation and definition at least in one character.